2012
DOI: 10.1021/ma3018876
|View full text |Cite
|
Sign up to set email alerts
|

Grafting Bimodal Polymer Brushes on Nanoparticles Using Controlled Radical Polymerization

Abstract: RAFT (reversible addition–fragmentation chain transfer) polymerization has been widely used to synthesize different polymer architectures such as polymer brushes on nanoparticles for incorporation into polymer nanocomposites. It is believed that these polymer brushes, with the same chemistry as the matrix polymer, can be employed to improve filler dispersion by compatibilizing unfavorable enthalpic interactions between the inorganic nanoparticles and their organic host matrices. However, monomodal brush graft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(157 citation statements)
references
References 34 publications
5
150
0
Order By: Relevance
“…In agreement with these predictions, recent experiments by Rungta et al, 2 where silica particles with bimodal polystyrene grafts, synthesized using step-by-step RAFT polymerization, were found be better dispersed in a monodisperse polystyrene matrix as compared to silica particles with monodisperse polymer grafts of length comparable to the long polymers in the bidisperse distribution. These promising results from theory and experiments should direct more groups to treat polydispersity in homopolymer ligands as a design parameter for stabilizing dispersions of polymer grafted particle in a polymer matrix.…”
Section: Feature Articlesupporting
confidence: 75%
“…In agreement with these predictions, recent experiments by Rungta et al, 2 where silica particles with bimodal polystyrene grafts, synthesized using step-by-step RAFT polymerization, were found be better dispersed in a monodisperse polystyrene matrix as compared to silica particles with monodisperse polymer grafts of length comparable to the long polymers in the bidisperse distribution. These promising results from theory and experiments should direct more groups to treat polydispersity in homopolymer ligands as a design parameter for stabilizing dispersions of polymer grafted particle in a polymer matrix.…”
Section: Feature Articlesupporting
confidence: 75%
“…(14) Kadla and coworkers were the first to demonstrate the application of ATRP to the synthesis of polymer-modified lignin derivatives. In particular the authors grafted Nisopropylacrylamide from kraft lignin to impart temperature-dependent solubility.…”
Section: Resultsmentioning
confidence: 99%
“…(8)(9)(10)(11)(12) Parallel progress in surface-initiated controlled radical polymerization has established a range of synthetic methodologies to facilitate the tethering of polymer chains with precisely controlled degree of polymerization, grafting density and even modality of polymeric tethers. (8,13,14) Recently our group demonstrated that the application of surfaceinitiated atom transfer controlled radical polymerization (SI-ATRP) facilitates the efficient synthesis of polymer tethered kraft lignin with high molecular polymeric tethers. (15) SI-ATRP is a particularly interesting technique in the context of filler modification because of its applicability to a wide range of monomer chemistries, the high level of control over molecular characteristics of tethered chains as well as its proven economic efficacy and scalability.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…[22][23][24] Homopolymer grafted to surface nanoparticles have been widely used to enhance dispersion and mixing into the polymer matrix by creating a chemical compatible layer between the nanoparticle and the polymer matrix. [25][26][27][28][29] Besides, variations in graft density () and graft chain length (N) provide different chain conformations of the shell, which affects the dispersion/aggregation of nanoparticles in the matrix. 30 was selected as the matrix.…”
Section: Introductionmentioning
confidence: 99%